Solvent-assisted surface engineering for high-performance all-inorganic perovskite nanocrystal light-emitting diodes - Wang, Lin (2020)
All-inorganic cesium halide perovskite nanocrystals have attracted much interest in optoelectronic applications for the sake of the readily adjustable band gaps, high photoluminescence quantum yield, pure color emission, and affordable cost. However, because of the ineluctable utilization of organic surfactants during the synthesis, the structural and optical properties of CsPbBr3 nanocrystals degrade upon transforming from colloidal solutions to solid thin films, which plagues the device operation. Here, we develop a novel solvent-assisted surface engineering strategy, producing high-quality CsPbBr3 thin films for device applications. A good solvent is first introduced as an assembly trigger to conduct assembly in a one-dimensional direction, which is then interrupted by adding a nonsolvent. The nonsolvent drives the adjacent nanoparticles connecting in a two-dimensional direction. Assembled CsPbBr3 nanocrystal thin films are densely packed and very smooth with a surface roughness of ∼4.8 nm, which is highly desirable for carrier transport in a light-emitting diode (LED) device. Meanwhile, the film stability is apparently improved. Benefiting from this facile and reliable strategy, we have achieved remarkably improved performance of CsPbBr3 nanocrystal-based LEDs. Our results not only enrich the methods of nanocrystal surface engineering but also shed light on developing high-performance LEDs.